Acute Toxicity of Clarias Gariepinus Fingerlings Exposed to 2,4-D Dimethylamine Salt - Idah Seiyaboh, Enetimi; Benafegha Enaregha, Esther; Chibueze Izah , Sylvester (Journal of Public Health International, 2020)
This study investigated the acute toxicity of Clariasgariepinusfingerlings. The fingerlings of Clariasgariepinuswere acclimatized for 1 week before the range-finding test was carried out at varying concentrations. Sublethal concentration (viz: 0.00ppm, 10.80 ppm, 18.00 ppm, 25.20 ppm, 32.40 ppm and 39.60 ppm of the 2,4-D Dimethylamine salt) were made in a rectangular aquarium. Each experimental concentration was carried out in triplicate with 10 fish each. The media were renewed at every 24 hours throughout the experimental duration viz: 96 hours. When the fish were introduced into the aquarium containing the toxicants, they exhibited some behavioural changes including opercular movement, air gulping and irregular swimming pattern. The mortality rate significantly increased as the concentration of the 2,4-D Dimethylamine salt increased for each of the exposure duration. The LC50 values at 24, 48, 72 and 96 were 86.15 ppm, 36.28 ppm, 18.72 ppm and 15.68 ppm, respectively. From the findings of this study, there is a need for exercise caution in the use of 2,4-D Dimethylamine salt based herbicides close to the aquatic ecosystem.
Keywords: Clariasgariepinus; Contaminants; Fish; Environmental health; Herbicides